The Main Proposals for the Content of Moral Theology in the Light of the Documents of the Council’s Renewal - Perz, Zygmunt (Studia Theologica Varsaviensia, 2020)
In the analyses to date only the conciliar guidelines concerning the basic issues of moral theology have been considered. %is does not mean at all that in the documents of the Council’s renewal there are no indications on many issues that are simply discussed in the detailed part of moral theology. Such a subject is the issue of religious freedom, which is linked to the treaty on faith. %e Council’s postulate is also to discuss the problem of the priesthood of the faithful in connection with the treatise on the honour of God (de religione). Moral issues of dialogue and ecumenism, including the participation of Catholics in the religious life of other faiths (communicatio in sacris), are awaiting elaboration. %e Council’s guidelines for the moralistic theologian also refer to the issue of contemporary social life, which has become the subject of the second part of the Gaudium et spes Constitution and were developed by Paul VI in the encyclical Populorum progressio. It seems superfluous to give a complete list of conciliar indications in the area of moral theology which relate to detailed topics of this theological discipline. In the Council’s renewal of theology, it is not a question of seeking new content, but of showing the “old” truths and principles in a living relationship with the revealed word of God, taking into account the needs of the human race of our time.